2010
DOI: 10.1016/j.theriogenology.2010.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Parthenogenetic development of domestic cat oocytes treated with ionomycin, cycloheximide, roscovitine and strontium

Abstract: The objective was to evaluate the parthenogenetic activation of domestic cat oocytes. Cumulus-oocyte complexes matured for 36 h were subjected to three protocols of parthenogenetic activation: Group 1 - ionomycin + cycloheximide; Group 2 - ionomycin + roscovitine; and Group 3 - ionomycin + strontium. As a control, a fourth group of oocytes were cultured in the absence of any activation agent. In all groups, embryos were cultured in SOFaa for 72 h after activation and evaluated for activation rate, cleavage, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
1
8
1
Order By: Relevance
“…Although researchers [13] , reported satisfactory morula attainment results (22-25%) in CHX exposed cat oocytes, in our study the lowest morula-blastocyst rates were obtained in electrical stimulation and calcium ionophore groups exposed to CHX in both immature and matured oocyte groups (2.7-3.7%). These differences may depend on the use of different activator agents such as roscovitine, and strontium in the Rascadoa et al [13] study. In contrast, others demonstrated that aging oocytes undergo artificial activation more rapidly than oocytes matured for shorter (24 h) intervals [36] .…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Although researchers [13] , reported satisfactory morula attainment results (22-25%) in CHX exposed cat oocytes, in our study the lowest morula-blastocyst rates were obtained in electrical stimulation and calcium ionophore groups exposed to CHX in both immature and matured oocyte groups (2.7-3.7%). These differences may depend on the use of different activator agents such as roscovitine, and strontium in the Rascadoa et al [13] study. In contrast, others demonstrated that aging oocytes undergo artificial activation more rapidly than oocytes matured for shorter (24 h) intervals [36] .…”
Section: Discussioncontrasting
confidence: 65%
“…Several different activating stimulants such as ionomycin, ethanol or electrical pulses, protein synthesis inhibitors such as cycloheximide (CHX) and 6-(Dimethylamino) purine (6-DMAP) are widely used to induce the artificial activation of mammalian eggs [12] . CHX and 6-DMAP are the protein synthesis inhibitors responsible for decreasing MPF and MAPK activity of the oocyte and restarting meiosis [13] . Alternatively, the effect of electrical stimulation influences movement of calcium ions in the oocyte and ionomycin establishes a complex that transports calcium ions through the membrane and into the oocytes [7,8,14] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we inferred that this was due to spontaneous oocyte activation. In that regard, parthenogenesis in cats has been described, with a rate varying from 2 to 35.5% [24,25]. This is apparently the first report of oocyte recovery and viability after short-term contraceptive treatment with deslorelin acetate in domestic cats.…”
Section: Discussionmentioning
confidence: 79%
“…The biotechnological methods of assisted reproduction in felids have been developed based on research into fertilization mechanisms and development of embryos in vitro . Cat embryos can be obtained in vitro by several methods: in vitro fertilization (IVF, ICSI) (Goodrowe et al , 1988; Johnston et al , 1989; Jewgenow et al , 1997; Pope et al , 1998; Ringleb et al , 2004), cloning (Shin et al ., 2002; Gómez et al , 2004) or artificial activation of oocytes (Grabiec et al , 2007; Rascado et al , 2010). In all of these methods, similar to IVF, activation of the oocyte is essential for triggering cleavage to form embryos.…”
Section: Introductionmentioning
confidence: 99%